Detection of Spargana on Ptyas korros in Sidoarjo - Ryan Bagaskara; Bambang Sektiari Lukiswanto; Adi Prijo Rahardjo; Emmanuel Djoko Poetranto; Setiawan Koesdarto; Mufasirin Mufasirin (Jurnal Medik Veteriner)
Ptyas korros or Indo-China Rat Snake is one of the snakes that are commonly hunted in Indonesia. This study aimed to identify Spirometra sp. on P. korros in Sidoarjo. A total of 18 snakes were collected within 3 months. Identification of Spirometra sp. was done using a native method, Semichen Acetic Carmine, and HE staining. As a results, 8 (44.4%) of 18 samples showed positive infection with Spirometra sp. The results of this study indicate the presence of spargana in P. korros in Sidoarjo and no adult Spirometra sp. was found.